2007
DOI: 10.1186/1477-7525-5-53
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Hurdles of Insulin Prescription (SHIP©): development, scoring and initial validation of a new self-administered questionnaire

Abstract: Background: Although insulin therapy is well-accepted by symptomatic diabetic patients, it is still often delayed in less severe patients, in whom injectable insulin remains under-used. A better understanding of patients' perception of insulin would eventually help physicians to adopt the most appropriate dialogue when having to motivate patients to initiate or to intensify insulin injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
1
22
0
2
Order By: Relevance
“…2005, Larkin et al. 2008); the hurdles of insulin prescription (Martinez et al. 2007); and a resistance to treatment questionnaire (Mishali et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2005, Larkin et al. 2008); the hurdles of insulin prescription (Martinez et al. 2007); and a resistance to treatment questionnaire (Mishali et al.…”
Section: Resultsmentioning
confidence: 99%
“…For example, participants listed a number of barriers regarding the details of the procedure, such as: ‘Do you think I can go and excuse myself (from my boss) to eat at the precise time?’ (Bogatean & Hancu 2004, p. 249); ‘takes time and energy’ and ‘[drawing up the] right amount [of insulin is] difficult’ (Larkin et al. 2008, p. 516); ‘Fear that treatment gets more complicated’ (Martinez et al. 2007, p. 4); ‘I just don’t have enough time for regular doses of insulin’ (Petrak et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were several questionnaires developed to assess patient perceptions of insulin therapy that could affect insulin adherence [13,[15][16][17][18][19][20], few of these studies assessed the association between the factors that could affect insulin adherence and levels of self-care activities in insulin injection in other than Western countries. A recent study found that insulin injection-related problems such as interference with daily activities, injection pain and embarrassment were independent risk factors for insulin omission [21].…”
Section: Introductionmentioning
confidence: 99%
“…Имеются литературные данные, показывающие, что не со всеми пациентами проводятся занятия по технике инъекций, но даже с теми, кто получает подобную информацию от меди-цинских работников, обсуждаются далеко не все важные аспекты правильного выполнения инъекций [24][25][26].…”
Section: обсуждение результатовunclassified